Kebakaran Hutan di Indonesia dan Proses Penegakan Hukumnya Sebagai Komitmen dalam Mengatasi Dampak Perubahan Iklim - Popi Tuhulele Tuhulele (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
Indonesia's commitment to reduce the impact of global climate change on theratifying conventions ujudkan with the UN on climate change (UNFCCC). Thismeans that Indonesia has the responsibility to demonstrate to the internationalcommunity as well as to peminpinannya komiten in addressing climate change impacts.However, the condition of Indonesia's forests continue to burn since the last 10-20 yearsthe international community raises questions about the commitment of Indonesia inpreventing climate change. Associated with these will be described in this paper abouthow the forest fires in Indonesia and the law enforcement process as a commitment totackling climate change. Discussion conducted in this peper systematically conducted inaccordance with the scope of the theme of this paper is about the commitment ofIndonesia and the implementation of law enforcement sepagai komitmnen indonsesiaagainst climate change